Answer:
(1) At t = 2.0 s tangential acceleration, a₁ = 4.8 m/s² and normal acceleration , a₂ = 230.4 m/s².
(2)15.8°
(3)0.55 s
Step-by-step explanation:
θ = 2 + 4t³
(1) the tangential acceleration a₁ = rα where α = angular acceleration = d²θ/dt² evaluated at t = 2.0 and r = 0.10 m
α = d²θ/dt² = 24t at t = 2 s
α = 24t = 24 × 2 = 48 rad/s²
a₁ = rα = 24tr = 0.10 m × 48 rad/s² = 4.8 m/s²
The normal acceleration a₂ = rω² where ω = angular velocity = dθ/dt = 12t² at t = 2.0 s
ω = 12t² = 12 × 2² = 48 rad/s
a₂ = rω² = 144rt⁴ = 0.1 × 48² = 230.4 m/s²
(2) The total acceleration a = √a₁² + a₂² = √[(24tr)² + (12t⁴r)²] = √[576t²r² + 144t⁸r⁴]. Since a₁ = a/2 ⇒ 24tr = √[576t²r² + 144t⁸r²]/2
48tr = √[576t²r² + 144t⁸r⁴]
squaring both sides
2304t²r² = 576t²r² + 144t⁸r²
2304t²r² - 576t²r² = 144t⁸r²
1728t²r² = 144t⁸r²
1728t²/144 = t⁸
t⁸ = 12t²
t⁸ - 12t² = 0
t²(t⁶ - 12) = 0
t² = 0 or t⁶ - 12 = 0
t = 0 or t⁶ = 12
![t = \sqrt[6]{12}\\ t = 1.51 s](https://img.qammunity.org/2021/formulas/physics/high-school/pd7zngfekr5hl64eposa9has248x12o4wi.png)
The tangential acceleration equals half the total acceleration at t = 1.51 s.
θ = 2 + 4t³ = θ = 2 + 4(1.51)³ = 15.77° ≅ 15.8°
(3) We find when a₁ = a₂
24tr = 144rt⁴
24t = 144t⁴
t⁴ = t/6
t⁴ - t/6 = 0
t(t³ - 1/6) = 0
t = 0 or t³ - 1/6 = 0
t = 0 or t = 1/∛6 = 0.55 s
So the tangential acceleration equals the normal acceleration at t = 0.55 s